The stereoselective formation of highly substituted CF3-dihydropyrans as versatile building blocks1. Issue 71 (14th September 2015) - Donslund, Bjarke S.; Monleón, Alicia; Larsen, Jesper; Ibsen, Lise; Jørgensen, Karl Anker
<x xml:space="preserve">Abstract</x> The dienamine-mediated formal inverse electron demand hetero Diels–Alder reaction providing optically active 5-bromo-6-(trifluoromethyl)-3, 4-dihydro-2H-pyrans is disclosed along with interesting transformations, affording a large variety of fully substituted dihydropyrans.